2005
DOI: 10.1016/j.jasms.2005.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase dissociation of oligoribonucleotides and their analogs studied by electrospray ionization tandem mass spectrometry

Abstract: Oligoribonucleotides (RNA) and modified oligonucleotides were subjected to low-energy collision-induced dissociation in a hybrid quadrupole time-of-flight mass spectrometer to investigate their fragmentation pathways. Only very restricted data are available on gas-phase dissociation of oligoribonucleotides and their analogs and the fundamental mechanistic aspects still need to be defined to develop mass spectrometry-based protocols for sequence identification. Such methods are needed, because chemically modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 27 publications
8
98
1
Order By: Relevance
“…The methoxy group at the 2′-position does not provide a bridging oxygen for the formation of a cyclic structure, thus the generation of c-and y-ions should be inhibited according to the published mechanism [29]. As this stands in contrast to our experimental data, there must be an alternative dissociation pathway accessible for 2′-O-methyl oligoribonucleotides.…”
Section: Fragmentation Of 2′-o-methyl Oligoribonucleotidescontrasting
confidence: 62%
See 2 more Smart Citations
“…The methoxy group at the 2′-position does not provide a bridging oxygen for the formation of a cyclic structure, thus the generation of c-and y-ions should be inhibited according to the published mechanism [29]. As this stands in contrast to our experimental data, there must be an alternative dissociation pathway accessible for 2′-O-methyl oligoribonucleotides.…”
Section: Fragmentation Of 2′-o-methyl Oligoribonucleotidescontrasting
confidence: 62%
“…Since the ON is fully 2′-modified, the presence of uninterrupted series of c-and y-ions is remarkable, in the sense that the generally accepted mechanism for dissociation of unmodified RNA by Tromp and Schürch does not apply [28,29]. The mechanism assumes the 2′-hydroxyl substituent to induce cleavage of the 5′-P-O bond, which leads to cand y-fragment ions, whereas the c-ion rearranges to the corresponding 2′-3′-cyclic phosphate.…”
Section: Fragmentation Of 2′-o-methyl Oligoribonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors suggested a 5=-POO cleavage mechanism involving the bridging of the 2=-OH proton to 5=-PO oxygen. In a recent study of the fragmentation of doubly deprotonated RNA tetramers, Tromp and Schürch [12] found that a 5=-POO bond was cleaved to a similar extend in absence of a 3=-adjacent nucleobase (replaced by hydrogen). They concluded that the nucleobase did not play a key role in 5=-POO cleavage.…”
mentioning
confidence: 99%
“…This ion pair is formed in a two-step mechanism triggered by the loss of a nucleobase [9]. In RNA, the primary fragmentation products are c-and y-ions, which has been explained by an alternative fragmentation mechanism involving the 2'-OH group [10]. Moreover, some of the synthetic modifications introduced in antisense oligonucleotides are also known to alter the gas-phase dissociation mechanism.…”
Section: Ms/ms Of Oligonucleotidesmentioning
confidence: 99%